Facilitating Trade and Structural Adjustment Thailand Experiences in Non-Member Economies - Tangkitvanich, Somkiat (OECD Trade Policy Papers, 2008)
This paper is the fourth of four country case studies which is a part of a broader research programme addressing trade and structural adjustment issues in non-member economies which was conducted as a follow-up to Trade and Structural Adjustment: Embracing Globalisation (OECD, 2005) which identified policies for successful trade-related structural adjustment. This paper studies the trade liberalisation experience of Thailand from the 1970s. The report consists of 6 main sections; Section 1 provides the introduction, while section 2 provides an overview of Thailand's growth experiences. Section 3 takes a closer look at the trade liberalisation and investment policies in Thailand: Thailand's initial trade regime and three phases of trade liberalisation: (1) initial tariff reforms (1982-84), (2) comprehensive tariff reform and its reversal with the Asian financial crisis (1993-), and (3) post crisis reforms (1999-) are studied. Section 4 looks at the changes in the investment and trade structure, while section 5 takes a closer look at structural adjustment in three sectors, the automotive and auto-parts sector, textile and clothing, and the telecom services sector. Section 6 concludes with lessons learnt. Thailand's experience confirms that a sound macroeconomic environment, sustainable public finances, a relatively stable political and economic environment, flexible labour markets and reliable infrastructure are crucial for economic growth. It provides an example of gradual trade liberalisation, and demonstrates the benefits of openness to international trade and foreign investment in correcting distortions in the economy